Profile of neonatal Thyroid Stimulating Hormone (TSH) levels in a Congenital Hypothyroidism Screening Program - Mardhah Sastri Utami; Resva Meinisasti (Indonesian Journal of Health Science, 2026)
Congenital hypothyroidism is an endocrine disorder in newborns characterized by thyroid hormone deficiency, which can lead to impaired growth and permanent neurological developmental disorders if not detected and treated early. Congenital hypothyroidism screening through the measurement of neonatal Thyroid Stimulating Hormone (TSH) levels is an important strategy for early detection to prevent these long-term consequences. This study aimed to describe the profile of neonatal TSH levels in the implementation of a congenital hypothyroidism screening program at a private hospital. This study employed a descriptive design with a retrospective approach. The data used were secondary data in the form of neonatal TSH examination results obtained from laboratory records during the period of April–July 2024. The sampling technique used was total sampling, including all data that met the inclusion criteria, with a total sample of 175 newborns. Data analysis was conducted using univariate analysis to describe the distribution of neonatal TSH levels based on the reference values for congenital hypothyroidism screening. The results showed that all neonatal TSH levels were within the normal reference range, with values ranging from 2 to 12 µIU/mL. No neonatal TSH levels ≥20 µIU/mL were found that would indicate suspicion of congenital hypothyroidism. These findings indicate that there were no signs of thyroid dysfunction among the newborns screened during the study period. The implications of this study confirm that the congenital hypothyroidism screening program has been implemented effectively as an early detection effort. Therefore, routine neonatal TSH screening should be maintained to prevent delayed diagnosis and to support optimal growth and development in infants.